2017
DOI: 10.1007/s00590-017-2020-y
|View full text |Cite
|
Sign up to set email alerts
|

Intra-operative fluoroscopic radiation exposure in orthopaedic trauma theatre

Abstract: IntroductionRadiation exposure from intra-operative fluoroscopy in orthopaedic trauma surgery is a common occupational hazard. References for fluoroscopy use in the operating room for commonly performed operations have not been reported adequately. This study aimed to report appropriate intra-operative fluoroscopy use in orthopaedic trauma and compare the effect of surgery type and surgeon grade on radiation exposure.MethodsData on 849 cases over an 18-month period were analysed retrospectively. Median and 75t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 14 publications
3
44
2
4
Order By: Relevance
“…By avoiding the use of fluoroscopy, the surgeon may decrease surgery duration, especially during the learning phase of the use of intraoperative fluoroscopy. 11,12 It will also eliminate potential risks associated with intraoperative irradiation of the surgical staff. Finally, it will reduce the cost of the equipment, and therefore the surgery, necessary for fixing the fracture.…”
Section: Discussionmentioning
confidence: 99%
“…By avoiding the use of fluoroscopy, the surgeon may decrease surgery duration, especially during the learning phase of the use of intraoperative fluoroscopy. 11,12 It will also eliminate potential risks associated with intraoperative irradiation of the surgical staff. Finally, it will reduce the cost of the equipment, and therefore the surgery, necessary for fixing the fracture.…”
Section: Discussionmentioning
confidence: 99%
“…also divided experience levels based on tiers of consultants, Staff Grade/Associate Specialists and Specialist training registrars. 32 Botchu et al . instead of using grade/tier, used the number of years practicing to define experience level.…”
Section: Grading Of Surgeon Experiencementioning
confidence: 99%
“…19,20,22 Two studies additionally reported the number of films/exposures taken. 25,32 One study used the number of films with part of surgeon’s body as a measure of radiation exposure. 25 This was expressed in terms of percentage of the total number of films.…”
Section: Outcomes Studiedmentioning
confidence: 99%
“…Other complications have been reported with distally locked constructs, including implant failure (0.2%), screw loosening and breaking, drill bit breaking (0.4%), soft tissue irritation, intramuscular haematoma and compartment syndrome. 10 , 40 , 44 , 45 , 46 Higher radiation exposure for the surgical team is also a factor to consider in distally locked nails. 45 …”
Section: Resultsmentioning
confidence: 99%
“… 10 , 40 , 44 , 45 , 46 Higher radiation exposure for the surgical team is also a factor to consider in distally locked nails. 45 …”
Section: Resultsmentioning
confidence: 99%